Theory of sampling (TOS) versus measurement uncertainty (MU) – A call for integration - Esbensen, Kim H.; Wagner, Claas (TrAC, Trends in analytical chemistry (Regular ed.), 2014)
•Critical appraisal of approaches to Measurement Uncertainty (MU).•Theory of Sampling (TOS) – the missing link in MU.•Untreated sampling errors result in uncontrollable, inflated estimates of MUtotal.•TOS alone should be responsible for the analytical aliquot (precedence over MU). We assess current approaches to measurement uncertainty (MU) with respect to the complete ensemble of sources affecting the measurement process, in particular the extent to which sampling errors as set out in the Theory of Sampling (TOS) are appropriately considered in the GUM and EURACHEM/CITAC guides. All pre-analysis sampling steps play an important, often dominant role in the total uncertainty budget, thereby critically affecting the validity of MU estimates, but most of these contributions are not included in the current MU framework. The TOS constitutes the only complete theoretical platform for dealing appropriately with the entire pathway from field sample to test portion. We here propose a way to reconcile the often strongly felt differences between MU and TOS. There is no need to debate terminology, as both TOS and MU can be left with their current usages.